Credit Risk Management Mechanisms in Social Lending Markets - Kisiel, Michał (Narzędzia zarządzania ryzykiem kredytowym na rynkach pożyczek społecznościowych, 2010)
Online social lending encompasses a range of markets that allow individual borrowers and lenders to engage in credit transactions without traditional intermediaries such as banks. The credit risk management tools are of great importance in the most of the social lending models. In this article the commonly used credit risk evaluation and management tools are reviewed. Some of them are new and might be incorporated to financial institutions' procedures: using peer pressure to enhance loan performance and the usage of social networking websites to gather creditworthiness assessment information. The study exposes also few problematic areas where P2P lending markets show their immaturity and that must be improved to ensure further growth of social lending phenomenon.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 64-77
Keywords: social lending; P2P lending; credit risk; credit risk management